Ethylene treatment of "Maekawa‐Jiro" persimmon affects peel characteristics and consequently, enables boil‐peeling. Issue 5 (17th March 2021) - Murakami, Satoru; Yamaguchi, Kazuki; Hashimoto, Nozomi
Abstract: In a previous study, we reported that ethylene treatment facilitated boil‐peeling in persimmons and in several other fruits; however, the mechanism underlying the facilitating effect of ethylene was not examined in detail. Thus, in this study, we investigated the effect of ethylene treatment on the peel characteristics of persimmons, that facilitated boil‐peeling, using chemical, genomic, and histochemistry analyses. The results of the study showed that the ethylene‐related genes, DK‐ACS1 and DK‐ACO2, and the pectinase‐active gene DKPG were not expressed, even though a minor increase in ethylene generation was observed after ethylene treatment. Conversely, significant accumulation of toluidine blue O and ruthenium red dyes were observed in the sarcocarp and exocarp of the fruits, indicating an increase in the quantity of polysaccharides, including pectic substances, at the site. The results also indicate that the increased cellulase activity observed in the pericarp of the fruits may be due to the aging of the fruits, and not necessarily as a result of ethylene treatment. Furthermore, ethylene treatment increased the quantity of polysaccharides, including pectic substances, directly below the pericarp, which caused the dissolution of the site, resulting in peeling. This study provides new insights on the effect of ethylene on boil‐peeling in persimmons and provides a foundation for future research studying the effect of heat treatment in the peeling of fruits or tomato. Abstract : Boil‐peeling in persimmons was possible because ethylene treatment increased the quantity of pectic substances in the pericarp of the fruit which resulted in the softening of the peel.